2020
DOI: 10.3354/dao03491
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of shrimp health and immunity with diets supplemented with combined probiotics: application to Vibrio parahaemolyticus infections

Abstract: The application of probiotics for disease control in aquaculture is now a convincing approach towards replacement of antibiotics, which can cause adverse effects in aquatic animals and humans. In this study, we combined 2 probiotics, Lactobacillus acidophilus and Saccharomyces cerevisiae, with shrimp feed to create 2 formulas (WU8 and WU9), which were fed for 10 d to juvenile shrimp Penaeus vannamei. The shrimps were then subjected to a challenge infection with Vibrio parahaemolyticus, the causative agent of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 36 publications
1
10
0
1
Order By: Relevance
“…as probiotic in Penaeus monodon Fabricius (the giant tiger shrimp) as an effective treatment against white spot diseases and vibriosis. Pooljun et al (2020) confirmed that enriched juvenile shrimp (Penaeus vannamei)-fed diets with L. acidophilus and S. cerevisiae mixture (1:1, at 10 8 and 10 9 CFU kg diet −1 ) impaired the adverse effects induced by Vibrio parahaemolyticus infection (acute hepatopancreas necrosis disease, AHPND) via improved hemocyte parameters, including the total hemocyte count, granular hemocytes percentage, and phenol-oxidase activity as well as highly upregulated hemocytes genes (Crustin and penaeidin) and led to high survival rate. Recently, de Souza et al ( 2020) investigated that allocated pacific white shrimp, Litopenaeus vannamei, in biofloc system (water contain beneficial bacterial strain) improved immune response against white spot syndrome virus (WSSV) infection through upregulated calreticulin, β-tubulin, and prophenol-oxidase genes in hepatopancreas cells.…”
Section: The Protective Role Of Lactic Acid Bacteria Against Viral Diseasesmentioning
confidence: 99%
“…as probiotic in Penaeus monodon Fabricius (the giant tiger shrimp) as an effective treatment against white spot diseases and vibriosis. Pooljun et al (2020) confirmed that enriched juvenile shrimp (Penaeus vannamei)-fed diets with L. acidophilus and S. cerevisiae mixture (1:1, at 10 8 and 10 9 CFU kg diet −1 ) impaired the adverse effects induced by Vibrio parahaemolyticus infection (acute hepatopancreas necrosis disease, AHPND) via improved hemocyte parameters, including the total hemocyte count, granular hemocytes percentage, and phenol-oxidase activity as well as highly upregulated hemocytes genes (Crustin and penaeidin) and led to high survival rate. Recently, de Souza et al ( 2020) investigated that allocated pacific white shrimp, Litopenaeus vannamei, in biofloc system (water contain beneficial bacterial strain) improved immune response against white spot syndrome virus (WSSV) infection through upregulated calreticulin, β-tubulin, and prophenol-oxidase genes in hepatopancreas cells.…”
Section: The Protective Role Of Lactic Acid Bacteria Against Viral Diseasesmentioning
confidence: 99%
“…In the last twenty years an increasing number of studies show improvements in growth, digestive enzymes and survival after bacterial challenge, changes in the gut microbiome, and enhanced immune capacity of P. vannamei following feeding with lactic acid bacteria alone or in combination with prebiotics, other probiotics, or immune stimulants (Chiu et al, 2007(Chiu et al, , 2021Vieira et al, 2008;Kongnum and Hongpattarakere, 2012;Nguyen et al, 2018;Zheng et al, 2018Zheng et al, , 2020Du et al, 2020;Pooljun et al, 2020;Kuo et al, 2021;Prabawati et al, 2022). Most studies report enhanced growth in the presence of probiotics (e.g., Chiu et al, 2021;Kuo et al, 2021), others (Bernal et al, 2017;Nguyen et al, 2018) including our current study, did not find evidence of such improvements.…”
Section: Discussionmentioning
confidence: 99%
“…such as Lactobacillus spp., could be used as effective alternatives to antibiotics for treating bacterial infections, especially V. harveyi infection in shrimp aquaculture [48]. Pooljun et al (2020) confirmed that, after feeding juvenile shrimp (Penaeus vannamei) with L. acidophilus and Saccharomyces cerevisiae mixture (1:1, at 10 8 and 10 9 CFU/kg feed), the adverse effects of acute hepatopancreas necrosis disease induced by V. parahaemolyticus infection were ameliorated by improving hemocyte parameters, including the THC, granular hemocyte percentage, and phenoloxidase activity, as well as by highly upregulating hemocyte genes (crustin and penaeidin), which lead to high shrimp survival rate [49].…”
Section: Discussionmentioning
confidence: 99%